Unprinted: publication beyond the press - Kohler, D; Wakelin, D; Domeisen, N; Jones, E; Mackay, M; Maxton, R; Moore, BM; Noble, K; Simon, FM; Haywood, D; Wojahn, D (Cambridge University Press, 2025)
This Element explores the idea of publication in media used before, alongside, and after print. It contrasts multiple traditions of unprinted communication in their diversity and particularity. This decentres print as the means for understanding publication; instead, publication is seen as an heuristic term which identifies activities these traditions share, but which also differ in ways not reducible to comparisons with printing. The Element engages with texts written on papyrus, chiselled in stone, and created digitally; sung, proclaimed, and put on stage; banned, hidden and rediscovered. The authors move between Greek inscriptions and Tibetan edicts, early modern manuscripts and AI-assisted composition, monasteries and courts, constantly questioning the term 'publication' and considering the agency of people publishing and the publics they address. The picture that transpires is that of a colourful variety of contexts of production and dissemination, underlining the value of studying 'unprinted' publication in its own right.